"Словарь української мови" за ред. Б. Д. Грінченка в інтегральному моделюванні розвитку лексики та лексикографії - Сніжко, Н.В. (Лексикографічний бюлетень, 2013)
«Словарь української мови» за ред. Б. Д. Грінченка – безцінне джерело вивчення історії національної мови та культури. Він є науковим підґрунтям для укладання нових словників, розвитку та формування сучасних напрямків інтегральних лінгвістичних досліджень. The article deals with analysis of the usage of Ukrainian Language Vocabulary by Boris Hrinchenko for research the history of development Ukrainian lexis and lexicography end XVIII – early XXI centuries. There are analyzed methodological problems of creation the Ukrainian Summary Word Index and an Integral Word Thesaurus where Vocabulary by Boris Hrinchenko plays the key role. The author accentuates the significance of Dictionary by Boris Hrinchenko to maintain the basis of nation language as well as to development of integral lexicography.